The Need and Use the Rural ICT Services in Iranian Rural Areas - Amir Mozafar Amini; Parnia Mosharaf; Mohammad Sadegh Ebrahimi (Journal of Education and Learning (EduLearn), 2015)
Nowadays, Internet access and use of information resources in all human societies are experiencing a rising trend, and different communities are used each with multiple infrastructures due to the benefits of ICT. The present study was based on applied research. In this research, a hybrid approach involving quantitative methods (survey) and qualitative (observation, interviews) was used. Statistical population of this study consists of two parts, the first part responsible for rural ICT offices, with a population of 125 people using Cochran Formula 80 subjects were selected as first sample, and the second part of the rural of first sample villages with a population of 84,836 people using Cochran formula and randomized-comparative method were studied as second sample. The questionnaire was subjected to reliability testing by using data collection in the pilot study with Cronbach’s Alpha value 0.73 to 0.95 for all variables. SPSS statistical software was used to analysis the data. The results of the study indicate that the overall performance of the agencies providing services to the rural was lower-middle in the offices in banking services has received first place, and the final ranking in the provision of health services. The results of study showed that rural employment, level education and family size effect on the rate of rural ICT offices.